Environmental Factors Driving Seed Hydration Status of Soil Seed Banks and the Implications for Post-fire Recruitment - Tangney, Ryan; Merritt, David J.; Miller, Ben P. (Frontiers in Plant Science, 2022)
Changes in fire regimes due to climate change and fire management practices are affecting the timing, length and distribution of vegetation fires throughout the year. Plant species responses and tolerances to fire differ from season to season and are influenced by species-specific phenological processes. The ability of seeds to tolerate extreme temperatures associated with fire is one of these processes, with survival linked to seed content moisture at the time of expo-sure. As fire is more often occurring outside historic dry fire seasons, the probability of fire occurring when seeds are hydrated may also be increasing. In this study we set out to under-stand the seasonal dynamics of seed hydration for seeds of Banksia woodland species, and how certain seed traits interact with environmental conditions to influence survival. We measured the moisture content of seeds buried to 2 cm in the soil seed bank for four common native species and one invasive species on a weekly basis throughout 2017, along with soil moisture content and environmental correlates. We constructed isotherms for seeds of each species and used these functions to model weekly variation in seed water activity and predict when seeds are most sensitive to soil heating. Using Generalised additive models (GAMs) we were able to describe approximately 67% of the weekly variance in seed water activity hydration and explored differences in hydration dynamics between species. These data, and the associated analyses, provides an opportunity to develop approaches to minimize seed mortality during fire and maximize seed bank response.